Organic functionality in responsive paramagnetic nanostructures - Duncan, Anna M.; Ellis, Connor M.; Smith, James P.; Leutloff, Lillian; Langton, Matthew J.; Davis, Jason J. (Frontiers in Chemistry, 2025)
Magnetic resonance imaging (MRI) has become an invaluable tool for diagnosing and monitoring a range of medical conditions, including cancer and cardiovascular disease, owing, in large part, to its high spatial resolution. Despite this, MRI suffers from an inherent low sensitivity, a drawback that can be mitigated through the use of exogenous contrast agents. Although molecular paramagnetic contrast agents are most commonly used, they suffer from significant limitations, including short circulation times, inadequate sensitivity, moderate (or no) tissue specificity, and potential toxicity. Recent advancements in nanomaterials research have paved the way for the development of paramagnetic nanoplatforms offering a promising alternative to these traditional chelates. Responsive contrast agents have gained attention due to their ability to generate local contrast in areas of particular interest, enabling the potential for disease-specific reporting where environmental factors including pH, ion concentration and biomolecule activity deviate from the norm. In addition to this, the generation of local or locality-specific contrast can help to overcome the intrinsic nonspecific nature of traditional contrast agents allowing for overall better treatment options. Purely organic nanoparticles, including those which are micellar, liposomal or dendritic and inorganic-polymer hybrids, can support step changes in MRI signal generation and its diagnostic potency by leveraging the specific and responsive characteristics of the organic components. This review seeks to illustrate how the integration of organic chemistry into magnetic nanostructures can enable responsive high-contrast generation.